Estimation of Loss of Iodine from Edible Iodized Salt During Cooking of Various Bangladeshi Food Preparations (Dhaka University Journal of Pharmaceutical Sciences, 2017)
Iodine is one of the essential micronutrients required for the normal mental and physical development of human beings. Low iodine intake exerts several detrimental effects on human health. The most serious effect of iodine deficiency is represented by possible damage to the fetus such as stillbirths, abortions and congenital abnormalities. According to the existing law, iodized salt should contain at least 15 ppm of iodine. However, iodine is lost significantly during cooking and few studies have been conducted to estimate such loss of iodine. Hence, in the present study, thirty recipes commonly cooked in Bangladeshi families were taken and by using colorimetric assay method, it was found that the mean losses of iodine during different cooking procedures were 13.28% for pressure cooking, 23.46% for boiling, 9.5% for deep frying and 5.18% for shallow frying. The results showed that the loss of iodine depends upon the type of cooking procedures and cooking time.Dhaka Univ. J. Pharm. Sci. 15(2): 161-165, 2016 (December)